2014
DOI: 10.1007/s13238-014-0070-z
|View full text |Cite
|
Sign up to set email alerts
|

USP33, a new player in lung cancer, mediates Slit-Robo signaling

Abstract: Ubiquitin specific protease 33 (USP33) is a multifunctional protein regulating diverse cellular processes. The expression and role of USP33 in lung cancer remain unexplored. In this study, we show that USP33 is down-regulated in multiple cohorts of lung cancer patients and that low expression of USP33 is associated with poor prognosis. USP33 mediates Slit-Robo signaling in lung cancer cell migration. Downregulation of USP33 reduces the protein stability of Robo1 in lung cancer cells, providing a previously unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 38 publications
0
42
0
Order By: Relevance
“…For example, ubiquitin-specific protease 33 (USP33) was shown to be down-regulated in breast cancer (YuasaKawada et al 2009), lung cancer (Wen et al 2014) and colorectal cancer (Liu et al 2016b). On the other hand, we previously reported the enhanced expression of ubiquitinspecific protease 7 (USP7) in ovarian cancer (Ma and Yu 2016), which revealed that different ubiquitin-regulated enzymes may show completely different functions in tumor regulation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ubiquitin-specific protease 33 (USP33) was shown to be down-regulated in breast cancer (YuasaKawada et al 2009), lung cancer (Wen et al 2014) and colorectal cancer (Liu et al 2016b). On the other hand, we previously reported the enhanced expression of ubiquitinspecific protease 7 (USP7) in ovarian cancer (Ma and Yu 2016), which revealed that different ubiquitin-regulated enzymes may show completely different functions in tumor regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The functional significance of USP33 has been investigated in breast, colon and lung cancer cells. USP33 can inhibit the migration of these cells by its deubiquitinating activity on Robo [38][39][40]. Here, we found that USP33 could deubiquitinate and stabilize PPM1A (Fig.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 54%
“…Recent studies have reported that USP33 may mediate oncogenic signaling through the Slit-Robo signaling pathway in colorectal cancer and breast cancer [18-20]. To further explore the potential mechanism that might be involved in the USP33-associated malignant progression of PTC, we firstly tested the protein expression patterns of Robo1 in PTC tissues, and identified the positive correlations between Robo1 and USP33 levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into consideration that USP33 is an enzyme catalyzing deubiquitinate process, the interaction with Robo1 may modulate its ubiquitinating status. Indeed, several studies have reported that the ubiquitination of Robo1 was negatively regulated by USP33 [20, 27]. However, we cannot ignore other potential effects by USP33-Robo1 interaction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation